Contemporary principles of hypoxia management in case of ARDS of various origin (Part 2) - A. V. Vlasenko; E. A. Evdokimov; E. P. Rodionov (Вестник анестезиологии и реаниматологии)
The objective: based on the literature review to demonstrate that when managing severe parenchymal acute respiratory failure, in addition to respiratory support it is necessary to use comprehensive non-respiratory and pharmacological methods of treatment, as well as various diagnostic and therapeutic measures including innovative medical technologies and involvement of specialists of different profiles.Results: the article presents procedures of rational integrated and personalized therapy in patients with acute respiratory failure which are aimed to improve treatment outcomes.